Retinopathy in Newly Diagnosed Type 2 Diabetics with a special stress on the importance of glycemic control (Bangladesh Journal of Medical Science, 2014)
Background: Diabetes mellitus (DM) is a major health problem with long-term microvascular and macrovascular complications responsible for the majority of its mortality and morbidity. The development and progression of diabetic complications are strongly related to the degree of glycemic control. The purpose of this study was to study, the incidence of retinopathy in newly diagnosed diabetics and its association with various risk factors with a special stress on role of HbA1c levels. Methods: We analysed 300 newly diagnosed type2 diabetics (diagnosed within 6 months). Patients were subject to detailed history, examination (including retinal examination), and investigations including serum creatinine, urinary micro-albumin, 24 hours urinary protein, HbA1c and ultrasonography. Results: Incidence of retinopathy in newly diagnosed type 2 diabetics was 30% (91/300). With increase in HbA1c, the incidence of retinopathy increased. All results were statistically proven. Conclusion: Incidence of retinopathy in newly diagnosed type2 diabetics is as high as 30%. Glycemic control is the an important factor contributing to development of this microvascular complications in diabetic patients. DOI: http://dx.doi.org/10.3329/bjms.v14i1.16535 Bangladesh Journal of Medical Science Vol.14(1) 2015 p.39-42